Differences between incarcerated and non-incarcerated patients who die in community hospitals highlight the need for palliative care services for seriously ill prisoners in correctional facilities and in community hospitals: A cross-sectional study. (January 2018) - Rothman, Alex; McConville, Shannon; Hsia, Renee; Metzger, Lia; Ahalt, Cyrus; Williams, Brie A
Background: Incarcerated populations worldwide are aging dramatically; in the United States, prisoner mortality rates have reached an all-time high. Little is known about the incarcerated patients who die in community hospitals. Aim: Compare incarcerated and non-incarcerated hospital decedents in California. Design: Cross-sectional study. Setting/participants: All state hospital decedents ( N = 370, 831) from 2009 to 2013, decedent age over time examined with additional data (2001–2013). Results: Overall, 745 incarcerated and 370, 086 non-incarcerated individuals died in California hospitals. Incarcerated decedents were more often male (93% vs 51%), Black (19% vs 8%) Latino (27% vs 19%), younger (55 vs 73 years), had shorter hospitalizations (13 vs 16 days), and fewer had an advance care plan (23% vs 36%, p < 0.05). Incarcerated decedents had higher rates of cancer, liver disease, HIV/AIDs, and mental health disorders. Cause of death was disproportionately missing for incarcerated decedents. The average age of incarcerated decedents rose between 2001 and 2013, while it remained stable for others. Conclusion: Palliative care services in correctional facilities should accommodate the needs of relatively young patients and those with mental illness. Given the simultaneous growth in the older prisoner population with the rising age of incarcerated hospital decedents, community hospital clinicians should be prepared to care for seriously ill, incarcerated patients. Significant epidemiologic differences between incarcerated and non-incarcerated decedents in this study suggest the importance of examining the differential palliative care needs of incarcerated patients in all communities.